SDSS-IV MaNGA : star formation cessation in low-redshift galaxies. I. Dependence on stellar mass and structural properties - Wang, Enci (2018)
We investigate radial gradients in the recent star formation history (SFH) of 1917 galaxies with 0.01 < z < 0.14 from the Mapping Nearby Galaxies at Apache Point Observatory project. For each galaxy, we obtain twodimensional maps and radial profiles for three spectroscopically measured parameters that are sensitive to the recent SFH: Dn(4000) (the 4000 Å break), EW(HδA), and EW(Hα) (the equivalent width of the Hδ absorption and the Hα emission line). The majority of the spaxels are consistent with models of a continuously declining star formation rate, indicating that starbursts occur rarely in local galaxies with regular morphologies. We classify the galaxies into three classes: fully star-forming (SF), partly quenched (PQ), and totally quenched (TQ). The galaxies that are less massive than 1010Me present at most weak radial gradients in the diagnostic parameters. In contrast, massive galaxies with a stellar mass above 1010Me present significant gradients in the three diagnostic parameters if they are classified as SF or PQ but show weak gradients in Dn(4000) and EW(HδA) and no gradients in EW(Hα) if they are in the TQ class. This implies the existence of a critical stellar mass (∼1010Me) above which the star formation in a galaxy is shut down from the inside out. Galaxies tend to evolve synchronously from the inner to the outer regions before their mass reaches the critical value. We have further divided the sample at a fixed mass by both bulge-to-total luminosity ratio and morphological type, finding that our conclusions hold regardless of these factors; it appears that the presence of a central dense object is not a driving parameter but rather a by-product of the star formation cessation process.